Laryngeal adenoid cystic carcinoma: Three cases reports - Cui, Yu (Medicine (Baltimore), 2019)
INTRODUCTION: Laryngeal adenoid cystic carcinoma (LACC) is an extremely rare malignant neoplasm. The etiology of LACC remains unknown, and it is characterized by multiple recurrences, slow progression, and late distant metastasis. This study aimed to provide more information regarding the characteristics, diagnosis, and treatment of LACC by analyzing 3 clinical cases and reviewing the literature on this topic. PATIENT CONCERNS: Here, we present all 3 cases of LACC within the period between 2010 and 2019. Dyspnea was the most commonly observed symptom in these patients, followed by hoarseness, pharyngeal paresthesia, and difficulty swallowing. DIAGNOSIS: All patients were pathologically confirmed as LACC. INTERVENTIONS: All the patients underwent a combined therapy of surgical resection plus external irradiation. OUTCOMES: The follow-up time was between 2 and 6 years; no local recurrence occurred in any of the 3 patients. Lung metastasis was found in 1 patient 6 years after surgery. CONCLUSION: LACC is usually a slowly progressing cancer; the main treatment methods are surgery and radiotherapy, and the adequate radiotherapy dose should usually be greater than 60 Gy. The 5-year disease-specific survival rate is high; however, distant metastasis may still occur in patients with LACC even beyond 5 years after treatment. Therefore, patients with LACC require long-term surveillance.